Evolution Characteristics of the Flows Around the Tibetan Plateau and the Relationship with the Climate in China in Winter - Zhang, Yongli; Zuo, Hongchao; Gao, Xiaoqing; Fan, Guangzhou; Lv, Shihua; Hua, Wei; Dong, Longxiang (Frontiers in Earth Science, 2022)
During the winter half-year (previous October–April), the mid-latitude westerlies flows around the Tibetan Plateau (TP) and generate a dynamic low-pressure trough on its south side and a high-pressure ridge on its north side. In this study, we define the vorticity perturbation as the difference between local vorticity and the meridionally-averaged vorticity. Then, the difference of averaged vorticity perturbation at 600 hPa in the two key areas where the trough and ridge are located is used to represent the intensity of the flows around the Tibetan Plateau (FAT). The evolution characteristics of FAT in the winter half-year, as well as in autumn, winter and spring, are analyzed. Moreover, under global warming, in winter the relationship of FAT to the precipitation and temperature in China are discussed. The results show that FAT steadily exists on both sides of TP during the winter half-year. With the north-south migration of the mid-latitude westerlies, the FAT gradually strengthens in autumn, with the strongest intensity and the widest range in winter, and begins to weaken in spring. The intensity of FAT (IFAT) has a decreasing trend and a quasi-4a period variation on the interannual scale in all the time, both of which are closely related to the mid-latitude westerlies upstream of TP. Represented by the winter when IFAT is strongest, the IFAT is significantly correlated to the change of precipitation and temperature in most parts of China under global warming, especially in the convergence area over central-eastern China. There is also a significant correlation between IFAT and the precipitation and temperature anomalies in Northwest China, TP, and Northeast China. This relationship between the FAT anomaly and the climate anomaly in China in winter can be well explained by analyzing the anomalies of large-scale circulation, outgoing longwave radiation and water vapor flux divergence. The FAT anomaly maybe one of the reasons for the climate extreme events in China in winter.